IgE reactivity to native and recombinant Hev b 13: An allergenic protein from Hevea brasiliensis latex - Arif Siti Arija M; Yeang H Y (IRRDB Conference: NR Industry: Responding to Globalization 7-8 September 2004, Kunming International Convention & Exhibition Center, China)
The newly named latex allergen, Hev b 13, had been thought to be a variant of Hev b 7 (a patatin homologue) because of the close similarity in molecular weight and isoelectric point of these two proteins. The fact that both proteins showed esterase activity added to the confusion. One key characteristic of Hev b 13 appeared to confirm its identity with Hev b 7, was that IgE binding of Hev b 13 could be inhibited by patatin. For a time, therefore, Hev b 13 was known as Hev b 7b. When the full cDNA sequence of Hev b 13 was elucidated, no translated amino acid sequence homology was found between Hev b 13 to patatin and Hev b 7. While Hev b 13 and patatin shared no common amino acid sequences, one characteristic that the two proteins did have in common was that they were both glycosylated. The inhibition of IgE binding to Hev b 13 by patatin was due primarily to cross-reactive carbohydrate determinants (CCD) on the two proteins. There was no IgE binding when deglycosylated and periodated Hev b 13 were used in ELISA reaction and Western blots. No IgE inhibition to native Hev b 13 was detected when deglycosylated patatin was used as the inhibitor. To study further the role of the Hev b 13 glycan in IgE-recognition, an unglycosylated recombinant version of the protein was synthesised in Escherichia coli, using the pMal-c2 vector. A protein of 86 kDa was obtained and this corresponded to the expected size of the MBP-Hev b 13 fusion protein. The recombinant protein was recognized by the monoclonal and polyclonal antibodies against Hev b 13, thus confirming its identity. However, the recombinant protein had no binding affinity to IgE. All these results point to the carbohydrate moiety of the glycoprotein playing a much more important role in IgE binding than the amino acid domain.
Keywords: Allergenic protein; Hev b 13; Hevea latex; IgE reactivity